2018
DOI: 10.1039/c8ra06028b
|View full text |Cite
|
Sign up to set email alerts
|

Natural iron ore as a novel substrate for the biosynthesis of bioactive-stable ZnO@CuO@iron ore NCs: a magnetically recyclable and reusable superior nanocatalyst for the degradation of organic dyes, reduction of Cr(vi) and adsorption of crude oil aromatic compounds, including PAHs

Abstract: For the first time, stable ZnO@CuO@iron ore nanocomposites (NCs) were green synthesized using magnetic iron ore as a natural substrate through an eco-friendly, simple and cost-effective method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Nasrollahzadeh et al reported a green protocol for the synthesis of 1‐carbamoyl‐1‐phenylureas in the presence of a recyclable and reusable Fe 3 O 4 @SiO 2 nanocatalyst in water as a green solvent . Sajjadi et al synthesized the magnetically nanocomposites using plant extracts and non‐toxic solvents as green and non‐corrosive nanocatalysts …”
Section: Introductionmentioning
confidence: 99%
“…Nasrollahzadeh et al reported a green protocol for the synthesis of 1‐carbamoyl‐1‐phenylureas in the presence of a recyclable and reusable Fe 3 O 4 @SiO 2 nanocatalyst in water as a green solvent . Sajjadi et al synthesized the magnetically nanocomposites using plant extracts and non‐toxic solvents as green and non‐corrosive nanocatalysts …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the xanthan gum as a thickening and stabilising agent is widely used in a wide variety of applications, which is basically a complex exopolysaccharide produced by plant-pathogenic bacteria [15,16], and has been used to support the deposition of the NPs and f ZnO/SiO 2 /xanthan NC. Additionally, many studies reported that the pomegranate seeds include the considerable amount of antioxidants and bioactive phytochemicals such as phenolics, flavonoids, proanthocyanidins and ascorbic acid [17][18][19][20][21][22][23]. The higher biological activity of NPs provides a larger surface area and preferential adsorption of the NPs.…”
mentioning
confidence: 99%
“…Recently, S. M. Sajadi and co‐workers have reported the green synthesis of metal nanocomposite catalysts using plant extract and iron ore and used it for the reduction of nitro compounds, degradation of organic dyes and removal aromatic hydrocarbons . They have also reported the biosynthesis Ag and Pd with excellent catalytic activity for cyanation and tetrazole formation from aryl halide .…”
Section: Methodsmentioning
confidence: 99%